Smoking habits in HIV-infected people compared with the general population in Italy: a cross-sectional study - Giuseppe Vittorio De Socio; Marta Pasqualini; Elena Ricci; Paolo Maggi; Giancarlo Orofino; Nicola Squillace; Barbara Menzaghi; Giordano Madeddu; Lucia Taramasso; Daniela Francisci; Paolo Bonfanti; Francesca Vichi; et al. (BMC Public Health, 2020)
Abstract Background Tobacco use is a leading cause of preventable diseases and death for all individuals, even more so for people living with HIV (PLWH), due to their status of chronic inflammation. To date, in Italy no study was performed to compare smoking habits in PLWH and the general population. We aimed to investigate smoking habits in PLWH, as compared to the general population. Methods Multi-center cross-sectional study. Smoking habits were compared between PLWH and the general population. PLWH were enrolled in the STOPSHIV Study. The comparison group from the general population was derived from a survey performed by the National Statistics Institute (ISTAT), with a stratified random sampling procedure matching 2:1 general population subjects with PLWH by age class, sex, and macro-area of residence. Results The total sample consisted of 1087 PLWH (age 47.9 ± 10.8 years, male 73.5%) and 2218 comparable subjects from the general population. Prevalence of current smokers was 51.6% vs 25.9% (p < 0.001); quitting smoking rate was 27.1% vs. 50.1% (p < 0.001) and the mean number of cigarettes smoked per day was 15.8 vs. 11.9 (p < 0.001), respectively for PLWH and the general population. Smoking and heavy smoking rates amongst PLWH were significantly higher even in subjects who reported diabetes, hypertension and extreme obesity (p < 0.001). Logistic regressions showed that PLWH were more likely current smokers (adjusted Odds Ratio, aOR = 3.11; 95% Confidence Interval (CI) =2.62–3.71; p < 0.001) and heavy smokers (> 20 cigarettes per day) (aOR = 4.84; 95% CI = 3.74–6.27; p < 0.001). PLWH were less likely to have quitted smoking (aOR = 0.36; 95% CI = 0.29–0.46; p < 0.001). Conclusion HIV-infected patients showed a higher rate of current smokers, a larger number of cigarettes smoked and a lower quitting rate than the general population. Our findings emphasize the need for smoking cessation strategies targeting HIV persons.